Energy investing for dummies - Hodge, Nick, 1983-; Siegel, Jeffrey, 1970-; DeHaemer, Christian (2013)
Hodge explains the ins and outs of all energy sectors, and how to incorporate them into business and investment plans. You'll find all you need to know to integrate the big three markets-- coal, natural gas, and oil-- into your investment portfolio.
Introduction -- Getting started with energy investing -- Oil and gas investments: greasing the global economy -- Investing in coal -- The nuclear option -- Investing in the future: modern energy -- The part of tens.
Includes index.
0
Keywords: Energy industries; Investments; Commodity exchanges